Pemberdayaan UMKM Turunan Nanas Melalui Platform Digital di Desa Belantaraya Kecamatan Gaung - Rahayu Putri, Eka Indah; Rahmat Saputra, Randi; Ruvita, Diana; Ulandari, Ratu; Mukhlis, Fezli; Sartika; Riskifitriadi; Agung; Rizkan, Muhammad; Suhardi; Suriansyah; Sakrani; M.Sopyan; Jumiati; Adi Putra, Bambang Sasmita (Indra Institute Research & Publication, 2025)
The Community Service Program (KKN) in Belantaraya Village, Gaung District, Indragiri Hilir Regency, focused on empowering Micro, Small, and Medium Enterprises (MSMEs) producing pineapple-based products such as dodol and jam. The main challenges faced by local entrepreneurs were limited marketing strategies, simple packaging, and the absence of business legality. This program was carried out through a participatory approach involving observation, interviews, mentoring, and training related to product innovation and digital marketing strategies. The results showed an increased awareness of MSME actors regarding the importance of business identity through logo design, improved and more hygienic packaging, and the utilization of digital platforms such as social media for product promotion. In addition, entrepreneurs were assisted in obtaining a Business Identification Number (NIB) as a form of legal recognition. Through this digital-based empowerment, pineapple dodol and jam products have greater potential to compete, expand their market reach, and contribute to the local economy